2010
DOI: 10.1002/humu.21366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating self-declared ancestry of U.S. Americans with autosomal, Y-chromosomal and mitochondrial DNA

Abstract: The current U.S. population represents an amalgam of individuals originating mainly from four continental regions (Africa, Europe, Asia and America). To study the genetic ancestry and compare with self-declared ancestry we have analyzed paternally, maternally and bi-parentally inherited DNA markers sensitive for indicating continental genetic ancestry in all four major U.S. American groups. We found that self-declared U.S. Hispanics and U.S. African Americans tend to show variable degrees of continental geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 65 publications
0
58
0
Order By: Relevance
“…Fifty-two ancestry informative marker (AIM) single nucleotide polymorphisms (SNPs) and 76 MS SNPs were genotyped using the TaqMan OpenArray genotyping technology (Life Technologies, Carlsbad, CA). AIM SNPs were selected from previously published studies [22][23][24][25][26][27] to cover all chromosomes. MS SNPs were selected from the latest GWAS 8 and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-two ancestry informative marker (AIM) single nucleotide polymorphisms (SNPs) and 76 MS SNPs were genotyped using the TaqMan OpenArray genotyping technology (Life Technologies, Carlsbad, CA). AIM SNPs were selected from previously published studies [22][23][24][25][26][27] to cover all chromosomes. MS SNPs were selected from the latest GWAS 8 and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…By default, genetic studies of US population samples categorize individuals as European American, African American, Hispanic, or Asian (42,51,74,94,105). In Ibero-America, such categorization of research subjects is not standard, but studies of this type have been performed for some urban population samples (particularly in Brazil) (70,72,93,101) and for certain historic isolates (e.g., African-derived Brazilian Quilombos) (79).…”
Section: Genetic Ancestry In European Americans and African Americansmentioning
confidence: 99%
“…1B). structure analysis (Pritchard et al 2000) of DNA samples from HEMn-LP and HEMn-DP cells using 24 ancestry-informative autosomal SNPs together with a worldwide reference data set (HGDP-CEPH) (Lao et al 2010) revealed a probable European and a probable Sub-Saharan African genetic origin of the respective cell donors (Supplemental Fig. S1).…”
Section: Characterization and Suitability Of The Melanocyte Cell Systemmentioning
confidence: 99%
“…Genotypes of rs7164220, rs7497270, rs58843292, rs72625136, and rs79494067 were determined by restriction digestion of PCR fragments. To infer the geographic origin/genetic ancestry of the cell-line donors, 24 autosomal SNPs sensitive to detect continental ancestry were genotyped via two SNaPshot (Applied Biosystems) multiplex reactions as described elsewhere (Lao et al 2010). The continental ancestry of the samples was recovered by performing a structure analysis (Pritchard et al 2000) in which data from the HGDP-CEPH panel served as reference, as described elsewhere (Lao et al 2010).…”
Section: Genotypingmentioning
confidence: 99%